Pregnancy Vitamin D Supplementation and Childhood Bone Mass at Age 4 Years: Findings From the Maternal Vitamin D Osteoporosis Study (MAVIDOS) Randomized Controlled Trial. (11th June 2022) - Curtis, Elizabeth M.; Moon, Rebecca J.; D'Angelo, Stefania; Crozier, Sarah R.; Bishop, Nicholas J.; Gopal‐Kothandapani, Jaya Sujatha; Kennedy, Stephen H.; Papageorghiou, Aris T.; Fraser, Robert; Gandhi, Saurabh V.; Schoenmakers, Inez; Prentice, Ann; et al.
ABSTRACT: In the Maternal Vitamin D Osteoporosis Study (MAVIDOS) randomized trial, vitamin D supplementation in pregnancy did not lead to greater neonatal bone mass across the trial as a whole, but, in a prespecified secondary analysis by season of birth, led to greater neonatal bone mass among winter‐born babies. Demonstrating persistence of this effect into childhood would increase confidence in a long‐term benefit of this intervention. We investigated whether antenatal vitamin D supplementation increases offspring bone mineralization in early childhood in a prespecified, single‐center follow‐up of a double‐blinded, multicenter, randomized controlled clinical trial based in the UK (MAVIDOS). A total of 1123 women in early pregnancy with a baseline 25‐hydroxyvitamin D level 25–100 nmol/L from three research centers (2008–2014) were randomized to 1000 IU/d cholecalciferol or matched placebo from 14 weeks of gestation to delivery. Offspring born at the Southampton, UK research center were assessed at age 4 years (2013–2018). Anthropometry and dual‐energy X‐ray absorptiometry (DXA) were performed (yielding whole body less head [WBLH] bone mineral content [BMC], areal bone mineral density [aBMD], bone area [BA], and body composition). Of 723 children, 564 (78.0%) children attended the 4‐year visit, 452 of whom had a useable DXA. Maternal vitamin D supplementation led to greater WBLH aBMD in the children compared with placebo (mean [95% confidence interval CI]: supplemented group: 0.477 (95% CI, 0.472–0.481) g/cm 2 ; placebo group: 0.470 (95% CI, 0.466–0.475) g/cm 2, p = 0.048). Associations were consistent for BMC and lean mass, and in age‐ and sex‐adjusted models. Effects were observed across the whole cohort irrespective of season of birth. Maternal‐child interactions were observed, with a greater effect size among children with low milk intake and low levels of physical activity. Child weight, height, and body mass index (BMI) were similar by maternal randomization group. These findings suggest a sustained beneficial effect of maternal vitamin D supplementation in pregnancy on offspring aBMD at age 4 years, but will require replication in other trials. © 2022 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.